Experimental infection of cattle with Listeria monocytogenes: Participation of purinergic metabolism in disease pathogenesis - Jaguezeski A.M.* (2018)
© 2018 Elsevier LtdThe objective of this study was to evaluate whether experimental infection with Listeria monocytogenes alters the activity of triphosphate diphosphohydrolase (NTPDase), 5′-nucleotidase, and adenosine deaminase (ADA) in cattle. Ten male Holstein breed cattle were divided in two groups of five animals each: a control group, and a group infected with a pathogenic strain of L. monocytogenes. We drew blood for platelets on days 0, 7 and 14 of the experiment. On the 14th day post infection (PI), the animals were euthanized. Brain, spleen and liver were processed for histopathological examination and measurement of enzyme activities. The five (n = 5/5) bovines experimentally infected by L. monocytogene were positive-PCR in hepatic tissue. In the brain, only four (n = 4/5) of these animals were positive-PCR for listeriosis. There were no differences in platelet counts between groups (P > 0.05). In platelets, NTPDase activity (with ATP and ADP as substrates) were higher on the 7th PI day in the infected group, whereas the activities of 5′-nucleotidase and ADA were higher on the 7th and 14th PI. In serum and liver, ADA activity was higher in infected animals, but was lower on day 14 PI in spleen. NTPDase activity (with ATP as substrate) was higher in the cerebellum of infected animals, but was lower in the cerebral cortex and medulla oblongata. NTPDase activity (with ADP as substrate) was lower in the cerebellum and cerebral cortex of infected animals, whereas 5′-nucleotidase was higher. ADA activity was lower in the cerebellum, cerebral cortex and medulla oblongata in infected animals compared with controls. In conclusion, there appears to be a protective immunomodulatory response in spleen and brain structures of cattle infected with L. monocytogenes.